ELECTRONIC-VOTING (E-VOTING) POLICY IN CONSISTENT GENERAL ELECTIONS TOWARDS A DEMOCRACY SYSTEM IN INDONESIA - Karmanis Karolan (Universitas Diponegoro, 2020)
Indonesia as a democratic country has entered the era of the millennium in the implementation of general elections simultaneously, it is necessary to utilize computer technology using the Electronic-Voting (E-Voting) method. Several regions in Indonesia have used the E-Voting method as a means of democracy which is applied at the hamlet and village head election levels. Village Head election policy with E-Voting as a new means of democracy through a touch of the monitor screen and E-Verification through voters' E-KTP. For example: Pemalang Regency (Ujunggede Village), Jembrana Regency in Bali (Mendoyo Dangin Tukad Village). Elections through e-voting must be designed as best as possible to realize the principles of direct elections, namely direct, general, free, secret (overflow) and honest and fair (fair) in direct elections. Electronic voting systems (e-voting) must be taken seriously and ensure transparency, certainty, security, accountability, and accuracy. In addition to technology readiness, of course, it must be supported by the readiness of the community in implementing this e-voting system in the future. The government's unpreparedness and lack of socialization of e-voting can also be a factor triggering failure in implementing this system.